PERSEPSI WIRAUSAHAWAN ATAS KONTRIBUSINYA TERHADAP PEREKONOMIAN DI KABUPATEN BANDUNG - Yazid, Naufal; Badriyah, Mila; Dana Kusuma, Suteja Wira (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2021)
Entrepreneurs have an important role for the economy of a region, especially in Kabupaten Bandung which has great potential for entrepreneurial development. The role of entrepreneurs for a country is to open new types of businesses and new jobs and play an important role in the ability to create and provide value-added products that have the courage to take risks, and innovate, and can be well organized to find and read market opportunities. This study aims to determine the perception of entrepreneurs on their contribution to the economy in Kabupaten Bandung, as well as to determine the contribution of the culinary sector and the fashion sector to the economy in Kabupaten Bandung. This research method uses qualitative methods with descriptive methods by distributing questionnaires and interviews to entrepreneurs in Kabupaten Bandung. The results of the study can be seen that the majority of respondents perceive that entrepreneurs have a positive contribution to the economy in Kabupaten Bandung. Entrepreneurs directly or indirectly have contributed actively in advancing the economy, then the culinary sector and the fashion sector are the sectors that have the greatest potential contribution to the economy in Kabupaten Bandung.Keywords: Perception, Entrepreneur, Contribution, Economy